The nun - Diderot, Denis, 1713-1784 (Oxford world's classics (Oxford University Press), 2005)
"This novel takes the life of a young girl forced by her parents to enter a convent as its subject matter and provides an insight into the effects of forced vocations"--Provided by publisher.